1988
DOI: 10.1111/j.1464-410x.1988.tb04366.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Unilateral Experimental Testicular Torsion on Spermatogenesis and Fertility

Abstract: Significant subfertility exists in patients following unilateral testicular torsion, implying bilateral testicular disease. Immunological activation has been detected after experimental torsion and the present study sought to demonstrate immunologically mediated effects on contralateral spermatogenesis following experimental torsion, as well as quantifying ipsilateral damage. Early and late effects of torsion on bilateral spermatogenesis were studied at 1 and 6 months in 10 groups each containing 20 rats. Gros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 21 publications
0
19
1
Order By: Relevance
“…Second, several studies have disclosed that if a twisted testis is not removed, a reduced sperm count is not uncommon. (11)(12)(13) In our study, the pain duration was significantly different between groups. Testicular ischemia typically presents with sharp pain and epididymo-orchitis presents with indolent or slowly progressive pain.…”
Section: Discussionmentioning
confidence: 45%
“…Second, several studies have disclosed that if a twisted testis is not removed, a reduced sperm count is not uncommon. (11)(12)(13) In our study, the pain duration was significantly different between groups. Testicular ischemia typically presents with sharp pain and epididymo-orchitis presents with indolent or slowly progressive pain.…”
Section: Discussionmentioning
confidence: 45%
“…Again it has been shown in a number of studies that testicular torsion induces progressive morphological and biochemical changes due to both ischemia and reoxygenation of the tissues [7][8][9]. Taking all these adverse effects of the torsion into account, it is clear that only prompt diagnosis and appropriate surgical intervention can save the affected testis.…”
Section: Discussionmentioning
confidence: 99%
“…Among these protective methods, to improve tolerance of the torsioned testicle to ischemia, externa cooling of the affected testis has been examined in some studies [1,9,10]. Following the first experimental study concerning the use of hypothermia in 1766 by John Hunter, increasing experience with this application has shown that hypothermia could prolong the functional ability of some parenchymatous organs such as the heart, lung, kidney, liver and pancreatic islet transplantation [1].…”
Section: Discussionmentioning
confidence: 99%
“…Related to the etiology of contralateral testicular damage and subsequent subfertility occurring after unilateral testicular torsion, some theories including deficient supply of testosterone from the remaining functional testis, damage of contralateral testis due to orchidopexy performed at surgery for testicular torsion and chronic abnormality of both testes due to a congenital defect which may predispose to torsion have been suggested, none of which has not been confirmed completely. Hormone levels and contralateral testicular biopsy evaluation were found to be normal and subfertile status has been shown in many patients who did not undergo orchidopexy during surgery [7, 8, 9]. Thus, it is now well accepted that unilateral testicular torsion produces bilateral testicular disease with subsequent abnormal semen analysis [5].…”
Section: Introductionmentioning
confidence: 99%